2017
DOI: 10.1016/j.chest.2016.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Human Mesenchymal Stem Cells in Patients With Idiopathic Pulmonary Fibrosis via Intravenous Delivery (AETHER)

Abstract: ClinicalTrials.gov; No.: NCT02013700; URL: www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
164
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(178 citation statements)
references
References 34 publications
(50 reference statements)
4
164
0
4
Order By: Relevance
“…Temporal relationship suggested stem cell treatment as the likely trigger. In the recent AETHER study, treatment emergent adverse events were those occurring within 4 weeks of stem cell treatment [10]; our case met that definition. The clinical course made infection unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temporal relationship suggested stem cell treatment as the likely trigger. In the recent AETHER study, treatment emergent adverse events were those occurring within 4 weeks of stem cell treatment [10]; our case met that definition. The clinical course made infection unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results of the AE-THER study revealed two deaths during the study period, one from IPF exacerbation and one from disease progression, over a 15-month period after IV stem cell therapy. Neither death was reported as being related to the study intervention [10]. However, due to the small samples, the diversity of disease states, and different methods employed, there is much information lacking regarding the short-term and long-term safety of the procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small phase I study of bone-marrow derived mesenchymal stem cell infusion in mild to moderate IPF patients showed no treatment related serious adverse events 76 , but there remain some concerns that stem cells 79 . Most precision medicine discussion to date has focused on molecular and genetic markers in identifying distinct endotypes 77 .…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…A small phase I study of bone-marrow derived mesenchymal stem cell infusion in mild to moderate IPF patients showed no treatment related serious adverse events 76 , but there remain some concerns that stem cells 79 . Most precision medicine discussion to date has focused on molecular and genetic markers in identifying distinct endotypes 77 .…”
Section: Stem Cell Therapymentioning
confidence: 99%